"Сумуємо тяжкою втратою науки…": вшанування смерті в археологічному співтоваристві УСРР другої половини 1920-х – початку 1930-х рр. - Яненко, А. (Місто: історія, культура, суспільство, 2020)
У статті розглянуто дії та заходи, спрямовані на вшанування колег-археологів і науковців-музейників, які пішли у засвіти у другій половині 1920‑х – на початку 1930‑х рр. На прикладі Данила Щербаківського, котрий учинив самогубство через неможливість продовжувати наукові студії в музеї, померлих Миколи Біляшівського, Василя Ляскоронського, Сергія Дложевського, Бориса Фармаковського, Сергія Гамченка та інших проілюстровано типові пропам’ятні практики тогочасного інтелектуального співтовариства: публічні поховання і панахиди, покладання квітів на могилу, виголошення прощальних промов, ушанування вставанням і хвилиною мовчання під час буденних зібрань наукових осередків, некрологи й меморіальні статті на шпальтах періодики, надсилання телеграм, поштівок, офіційних і приватних листів із висловленням щирого співчуття і жалю через втрату, створення і діяльність спеціальних комісій і комітетів, встановлення анотованих дощок і надання структурним підрозділам наукових установ імені покійного інтелектуала, влаштування виставок, клопотання про надання пенсій родинам покійних, присвяти у фахових виданнях та посмертні публікації наукових студій. Залучено до наукового обігу маловідомі документи, що засвідчували вияв посмертної шани, – некрологи, офіційні та приватні звернення, світлини. Наголошено, що практики вшанування почасти виконували функцію громадянського протесту проти несправедливості, свавілля, нехтування принципами професійності й людяності, функцію опору репресивній і антигуманній політиці тоталітарного режиму. The article deals with actions and activities aimed at paying tribute to colleagues – archaeologists and museum research workers, who step out during the second half of the 1920s and early 1930s. Examples of typical memorable practices in the intellectual community are given. Civil funerals and laying flowers on the grave were a characteristic memorial phenomenon. The intellectual community was significantly affected by the loss of Mykola Biliashivskyi (April 1926), Danylo Shcherbakivskyi (June 1927), Vasyl Liaskoronskyi (January 1928), Borys Farmakovskyi (July 1928), Serhii Hamchenko (October 1932), etc. In funeral public speeches, archaeologists focused not only on the scientific achievements of the late, their contribution to the development of archeology, museology, art history, but also emphasized the deceased colleagues’ virtues. The dead men were honored by standing up and a moment of silence during the daily meetings of intellectual centers – departments, presidiums, research councils etc. Deep sadness over the loss of co-workers, condolatoryence to friends and relatives were publicly expressed in the press, obituaries and memorial articles were published. Colleagues addressed telegrams, postcards, official and private letters to the institution, where the late worked, or to his closest friends, expressing their sincere compassion for the loss. Special commissions or committees were sometimes set up to coordinate commemorative events after an intellectual’s death. Honor tribute was also paid through the installation of memorial plaques or giving the structural units of research institutions the name of the deceased intellectual. Temporary expositions were prepared for the anniversaries of death. The intellectual community representatives were petitioning for pensions for the families of the deceased. Dedications in professional editions and posthumous publications of the researchers’ studies were a common practice of post-mortem honoring of scientists. Little-known documents – manifestations of posthumous honor – obituaries, official and private addresses, photos are introduced into scientific use. It was emphasized that the practices of honoring also served as a civil protest against injustice, arbitrariness, disregard for the principles of professionalism and humanity, as well as were resistance to the repressive and inhumane policies of the totalitarian regime.